Need Analysis for Developing a STEM-Based Student Worksheet Application - Fadillah Rahmayani; Menza Hendri; Dian Pertiwi Rasmi (Pendidikan Kimia Unimus, 2021)
This study aims to analyze and determine the needs of teachers and students for a learning media development in the form of a STEM-based student worksheet application in . Data obtained through observation, interviews and student learning style questionnaires given to teachers and students of SMA N 1 Muaro Jambi. Teachers need an interesting and interactive learning media that can attract students' interest, while students need learning media that combines all aspects of visual, audiotorial and kinesthetic learning styles which are obtained from questionnaires.that students have visual, kinesthetic and audiotorial learning styles with a percentage of 58.3%, 58.3% and 52.8%. So thatResearchers will develop student worksheets in digital form that refer to the results of the learning style analysis. Products produced are in the form of android and based on STEM.